Diseño de un malecón en la parroquia El Salto en la ciudad de Babahoyo - Ortiz Moran, Harrynson Miguel (2024)
The aim of this thesis project is to enhance the quality of life of the inhabitants of El Salto, a city in Babahoyo, by creating a waterfront promenade to boost tourism in the coastal region. Moreover, it will be approached holistically, taking into consideration both the functionality and aesthetics of the space, as well as its harmonious integration with the natural and built environment. Efforts will be made to maximize the utilization of sustainable technologies and eco-friendly materials, in order to minimize environmental impact and promote the conservation of natural resources. Emphasis will be placed on sustainability and universal accessibility, ensuring that all individuals can fully enjoy its amenities. To achieve this, a thorough analysis of the environmental surroundings will be conducted, along with a study of the needs and preferences of the local community. Subsequently, the architectural design of the promenade will be executed, ensuring seamless integration with the surrounding landscape and its functionality for various activities and purposes. It is anticipated that this project will make a significant contribution to the tourism development of the region, while fostering social inclusion and environmental conservation. It is expected that the design of this promenade will not only enhance the quality of life of the local residents by providing them with new recreational opportunities but will also boost tourism in the region by attracting national and international visitors, and creating new sources of income for the community.